Hitler : diagnosis of a destructive prophet - Redlich, Fredrick C., 1910-2004 1910-2004 (Oxford Univ. Press, 1999)
Adolf Hitler unleashed a nightmare of terror in Europe that changed the course of history and forever altered our conception of human nature. But how is it possible to understand Hitler? Hitler: Diagnosis of a Destructive Prophet begins to answer that question by providing the first analysis of Hitler's life by a trained MD and practicing psychiatrist. Fritz Redlich, M.D., provides a full-length biography of Hitler, focusing especially on his medical and mental history and showing us precisely how Hitler's physical and mental health influenced his beliefs and behavior.